Phenotypic plasticity and modularity allow for the production of novel mosaic phenotypes in ants. Issue 1 (December 2015) - Londe, Sylvain; Monnin, Thibaud; Cornette, Raphaël; Debat, Vincent; Fisher, Brian; Molet, Mathieu
Abstract Background The origin of discrete novelties remains unclear. Some authors suggest that qualitative phenotypic changes may result from the reorganization of preexisting phenotypic traits during development (i.e., developmental recombination) following genetic or environmental changes. Because ants combine high modularity with extreme phenotypic plasticity (queen and worker castes), their diversified castes could have evolved by developmental recombination. We performed a quantitative morphometric study to investigate the developmental origins of novel phenotypes in the antMystrium rogeri, which occasionally produces anomalous 'intercastes.' Our analysis compared the variation of six morphological modules with body size using a large sample of intercastes. Results We confirmed that intercastes are conspicuous mosaics that recombine queen and worker modules. In addition, we found that many other individuals traditionally classified as workers or queens also exhibit some level of mosaicism. The six modules had distinct profiles of variation suggesting that each module responds differentially to factors that control body size and polyphenism. Mosaicism appears to result from each module responding differently yet in an ordered and predictable manner to intermediate levels of inducing factors that control polyphenism. The order of module response determines which mosaic combinations are produced. Conclusions Because the frequency of mosaics and their canalization around a particular phenotype may evolve by selection on standing genetic variation that affects the plastic response (i.e., genetic accommodation), developmental recombination is likely to play an important role in the evolution of novel castes in ants. Indeed, we found that most mosaics have queen-like head and gaster but a worker-like thorax congruent with the morphology of ergatoid queens and soldiers, respectively. Ergatoid queens ofM. oberthueri, a sister species ofM. rogeri, could have evolved from intercastes produced ancestrally through such a process.